Hampstead Buddhist Vihāra - Webb, Russell (Contemporary buddhism, 2016)
The author offers a brief history of the Hampstead Buddhist Vihāra, a residence and Dhamma centre purchased by the English Sangha Trust (EST) as part of a strategy to establish an indigenous British bhikkhu Sangha. Drawing on official publications of the EST, other contemporary documents and personal reminiscence, the narrative runs from the initial founding through to the sale of the properties accrued, leading to the establishment of rural monastic residences and retreat centres including Chithurst Forest Monastery and Amaravati. The activities of the HBV, including ordinations and publications, are also reviewed, the whole offered as documentation of details of one of the early attempts to establish the Sangha in the West.